Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/bkcs.12674
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of the S,N‐heteroacene‐based nonfullerene by introducing the fluorine atom for efficient high‐performance organic solar cells

Abstract: Fluorination has been established as an effective structural modification strategy to influence properties and has attracted attention in organic solar cells. Here, we design and synthesize three fused‐ring electron acceptors based on ladder‐type pentacyclic heteroacenes as the electron‐rich unit and 1,1‐dicyanomethylene‐3‐indanones with 0–2 fluorine substituents as the electron‐deficient units. Among these three molecules, two fluorine substituents nonfullerene acceptor, DTP‐2F exhibit strong absorption with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The primary effect of halogenation can be seen through the HOMO/LUMO energies, optical band gap, maximum absorption wavelength, morphology, and charge transfer efficiencies. Many studies 44,[132][133][134][135][136][137][138][139][140][141][142][143][144][145] have found that the addition of a halogen to the ICN terminal group results in down-shifting of the HOMO and LUMO energies. This can lead to smaller energy offsets with the donor material and improves V OC .…”
Section: Halogenation Vs Non-halogenationmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary effect of halogenation can be seen through the HOMO/LUMO energies, optical band gap, maximum absorption wavelength, morphology, and charge transfer efficiencies. Many studies 44,[132][133][134][135][136][137][138][139][140][141][142][143][144][145] have found that the addition of a halogen to the ICN terminal group results in down-shifting of the HOMO and LUMO energies. This can lead to smaller energy offsets with the donor material and improves V OC .…”
Section: Halogenation Vs Non-halogenationmentioning
confidence: 99%
“…Furthermore, halogenated NFAs can reduce the optical band gap, thus red-shifting the absorption towards the near-IR region and improving the J SC . 44,132,[134][135][136][137][138][139][141][142][143][144][145][146][147][148][149][150][151][152] Aside from the optical and energetic improvements of halogenated NFAs, halogenation can also enhance the film morphology. The high polarizability of halogens leads to reduced π-π stacking distances in NFAs 44,136,[139][140][141]144,148 , allowing for more efficient charge transfer and increasing the crystallinity of the blend film.…”
Section: Halogenation Vs Non-halogenationmentioning
confidence: 99%
“…Based on a ladder-type S, N-heteropentacene consisting of four fused thiophene rings and one pyrrole ring, Tan et al developed a novel A-D-Astructured FREA with IC-2F as the end groups, named DTP-C17-4F, which showed a strong near-infrared absorption with an optical bandgap of 1.38 eV and a LUMO level of -4.16 eV. 113 When blended DTP-C17-4F with the polymer donor PM6, the optimal device demonstrated a J sc of 21.17 mA cm −2 , a V oc of 0.69 V, and a FF of 61.1%, resulting in a PCE of 8.94%. Compared to SN6IC-4F containing three fused thiophene rings and two pyrrole rings in the donor core, DTP-C17-4F exhibited a larger optical bandgap and a lower-lying LUMO level, resulting in lower J sc and V oc in corresponding OSC devices.…”
Section: Pyrrole-containing A-d-a-type Freas With Sp 3 -Carbon-free S...mentioning
confidence: 99%
“…In recent times, there has been a notable upsurge in the demand for optoelectronic applications, propelling research into organic luminophores as distinguished functional materials. [1][2][3] Of particular significance is the extensive inquiry into ortho-closo-carboranes that incorporate π-conjugated organic luminophores. These materials have garnered substantial attention and have been the subject of extensive scrutiny in fields such as optoelectronics 4,5 and sensory devices 6,7 because of their exceptional thermal and chemical stabilities and unique photophysical attributes.…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, there has been a notable upsurge in the demand for optoelectronic applications, propelling research into organic luminophores as distinguished functional materials 1–3 . Of particular significance is the extensive inquiry into ortho ‐ closo ‐carboranes that incorporate π‐conjugated organic luminophores.…”
Section: Introductionmentioning
confidence: 99%